Faktor Yang Berhubungan Dengan Pelaksanaan Inisiasi Menyusu Dini Pada Ibu Post Partum - Kurniasari, Siela; Ajeng, Lumastari; Titisari, Ira (STIKES Karya Husada Kediri, 2025)
Background: Two thirds of infant deaths occur during the neonatal period. IMD can reduce the risk of infant death by 22%. However, the IMD in 2018 was 58.2%, which was not optimal. This research is to determine the factors related to the implementation of IMD Methods: a literature review with a Systematic Mapping Study approach obtained from the Google Scholar and PubMed databases. Results: The results of the review show that factors related to the implementation of IMD include the birth process, knowledge, level of education, family support and support from health workers. Conclusion: : The dominant factors related to IMD in postpartum mothers are the birth process and support from health workers. Limitations in the population of articles are that the bias is too large because the age of the baby is up to 24 months